An investigation of error awareness in healthy ageing and a non-invasive approach to its amelioration - Harty, Siobhán (Trinity College (Dublin, Ireland). School of Psychology, 2014)
Population ageing has become a global phenomenon. This demographic change flags the remarkable developments made by humanity in recent history, but it also constitutes one of the most challenging problems for contemporary society, as coincident with ever increasing life expectancies, are increasing rates of age-related cognitive decline. Non-pathological ageing is accompanied by several cognitive and brain changes that manifest in multiple dimensions. On the one hand, older adults have improved regulation of emotion, better vocabulary, better culture-related knowledge, and have better life satisfaction, compared to younger adults. On the other, they have reduced acuity of the senses, they require more time to both process, and respond to, sensory information, and invariably, they undergo declines in a number of other important physical and cognitive capacities. As the deterioration of older adults’ cognitive capacities begins to occur, the ability to monitor and evaluate the success of their cognitive processes is of paramount importance for detecting errors, and calibrating their daily activities to suit their strengths and weaknesses.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin